PEMASARAN BERAS ORGANIK DI KECAMATAN MOILONG KABUPATEN BANGGAI - Muala, Bakri; Mukhlis, Mukhlis (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to determine the marketing margin of rice. Respondents in this study were rice farmers in Moilong sub-district, Banggai Regency, the determination of respondents was carried out deliberately by considering that Batui Selatan sub-district was the center of organic rice production in Banggai Regency, The data analysis used was quantitatively by calculating marketing margins, the results showed that the rice marketing channel from farmers was handed over to intermediary traders and directly to consumers. The marketing margin of rice was IDR 1000 rupiah where the selling price from rice farmers to intermediary traders was IDR. 14,000 and the selling price back to consumers was IDR 15,000. The results showed that the efficiency of the rice marketing channel in Moilong District has a value of 40%, this figure is below 50% which means that the marketing channel is in the efficient category.